Why Did the Earwitnesses to the John F. Kennedy Assassination Not Agree About the Location of the Gunman? - McFadden, Dennis (Frontiers in Psychology, 2021)
Earwitnesses to the 1963 assassination of President John F. Kennedy did not agree about the location of the gunman even though their judgments about the number and timing of the gunshots were reasonably consistent. Even earwitnesses at the same general location disagreed. An examination of the acoustics of supersonic bullets and the characteristics of human sound localization help explain the general disagreement about the origin of the gunshots. The key fact is that a shock wave produced by the supersonic bullet arrived prior to the muzzle blast for many earwitnesses, and the shock wave provides erroneous information about the origin of the gunshot. During the government's official re-enactment of the JFK assassination in 1978, expert observers were highly accurate in localizing the origin of gunshots taken from either of two locations, but their supplementary observations help explain the general confusion of the earwitnesses to the assassination itself.